PENGARUH KONFLIK DAN MOTIVASI KERJA TERHADAP ETOS KERJA DAN IMPLIKASINYA PADA KINERJA KARYAWAN - TAKWIM, R. IIM (IMAGE : Jurnal Riset Manajemen, 2012)
The influence to conflict and job motivation on the job Ethos and their implication on employee’s performance. It is found that the employee’s performance  tend to decrease This matter is caused by lack of multiple complex of conflict and job motivation, so that it causes the decreasing of job ethos which implicates to the low of  employee’s performance. The characteristics measured from each responden are conflict, motivation, job etho’s , employee’s performance and their demographic characteristics.